Deu match: o encontro entre formação e ocupação garante melhores salários? - Oliveira, Alícia Araújo Amaral de (2024)
The aim of this dissertation is to investigate whether finding a job that is compatible with academic training leads to better salaries, based on an indicator that captures how close the graduate is to their expected occupation. To do this, an academic database is combined with information from the Brazilian formal labor market and, unlike previous literature, this analysis is enhanced by using the median of the grades obtained during graduation as the main instrument for controlling individual aptitudes. Through the estimation of quantile regression models with instrumental variables, segmented for men and women, the results show that the greater the combination of the stock of productive factors assimilated during graduation with the activities required by the position held in the market, the higher the salary earned by the worker. The results also document a small impact of proximity on income for male workers and non-significant impacts at the ends of the quantiles. The opposite scenario is observed among women, and the match proves to be more important for those who are concentrated at the bottom of the income distribution. The occupational match is expected to act as a reducer of the wage inequalities observed between male and female workers.